Blood-based Nutritional Risk Index for Cognition in the Nutrition and Brain Aging Study (NBAS): Emphasis on n-3 PUFA, Vitamin D and Homocysteine (P14-005-19). (13th June 2019) - Gouskova, Natalia; Bichsel, Aline; Dodge, Hiroko; Donohue, Juliana; Silbert, Lisa; Kaye, Jeffrey; Bowman, Gene
Abstract: Objectives: Nutrients and their metabolites have interactive qualities that may be harnessed for prevention of cognitive decline. Simultaneous modulation of one-carbon, fatty acid and vitamin D metabolism (25-OH-D) may offer neuroprotection. We examined whether n-3 polyunsaturated fatty acids (n-3 PUFA), 25-OH-D, and homocysteine (HCy) formed into a Nutritional Risk Index (NRI) can explain cognitive performance of older non-demented adults. Methods: The NBAS enrolled older participants from the NIA-Layton Oregon Alzheimer's Disease Center aging studies with serum samples available yielding 306 cognitively characterized older adults. Plasma fatty acids were quantified by GC-FID and 25-hydroxyvitamin D and homocysteine by LC-MS/MS. Nutritional risk defined as population nutrient biomarker tertiles with NRI calculated as the number of nutrient biomarkers meeting a sub-optimum criterion with scores ranging from 0 to 3. Global and domain specific cognitive z-scores were fit with multivariate linear regression models and NRI as the primary exposure of interest. Results: Mean age was 85.8 (7.6) years, MMSE was 27.8 (2.8) and 70% were female. Sixty-five % met criteria for 'nutritional risk' (NRI ³ 1: 193/293). Participants with optimum nutritional status exhibited superior global cognitive performance (NRI-0: mean global z-score ± SE = 0.10 ± 0.097) while each addition NRI point score associated with an incremental decrease in cognitive performance (NRI-1: 0.02 ± 0.09; NRI-2: −0.23 ± 0.13; NRI-3: −0.53 ± 0.19, P for trend = 0.002). Significant and similar trends were seen in specific cognitive domains, including attention (NRI-0: mean z-score ± SE = 0.20 ± 0.11; NRI-1: 0.02 ± 0.10; NRI-2: −0.32 ± 0.13; NRI-3: −0.38 ± 0.19, P for trend < 0.001) and executive function (NRI-0: mean z-score ± SE = 0.15 ± 0.10; NRI-1: −0.09 ± 0.10; NRI-2: −0.15 ± 0.13; NRI-3: −0.55 ± 0.20, P for trend = 0.002). Conclusions: The Nutritional Risk Index representing plasma n-3 PUFA, 25-OH-D and HCy explains significant variance in the cognitive performance of older adults, particularly attention and executive skills. These results in exceptionally healthy older adults suggest that cognitive performance is superior in those with plasma EPA + DHA wt% ≥ 2.53, 25-OH-D ≥ 25 ng/ml, and HCy < 11.57 umol/L. Funding Sources: Nestle Institute of Health Sciences, Hinda and Arthur Marcus Institute for Aging Research, NIA-Layton Aging & Alzheimer Disease Center, Department of Veterans Affairs.